2019
DOI: 10.1109/jsac.2019.2909076
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue on Artificial Intelligence and Machine Learning for Networking and Communications

Abstract: I. INTRODUCTION R ESEARCH in large-scale networking systems has been shaped and will continue to be guided by specific characteristics of applications and the underlying platforms and infrastructures. On the one hand, applications are growing at an accelerated pace, which is fundamentally unpredictable in both breadth and depth. On the other hand, the underlying networking has been the focus of a huge transformation enabled by new models resulting from virtualization and cloud computing. This has led to a numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The database of this architecture is composed of two parts: client application program and database server program, which are called foreground program and background program, respectively. The whole system consists of electromyogram collector, interface card, synchronizer and electromyogram acquisition, and analysis software [18]. For collective events, the tactical cooperation and tactical choice between athletes are important factors that determine the competition.…”
Section: Methodsmentioning
confidence: 99%
“…The database of this architecture is composed of two parts: client application program and database server program, which are called foreground program and background program, respectively. The whole system consists of electromyogram collector, interface card, synchronizer and electromyogram acquisition, and analysis software [18]. For collective events, the tactical cooperation and tactical choice between athletes are important factors that determine the competition.…”
Section: Methodsmentioning
confidence: 99%
“…Also, due to the fact that different parts of the network interact with each other, it is necessary to consider all parts of the network together to optimize the total energy consumption. Machine learning (ML) are new approaches to solve optimization problems in all domains, e.g., network domain, that have recently received a great deal of attention [14]- [16]. ML, due to its data-driven nature, automatically learns the network and communication environment and dynamically adapts protocols without human intervention [14]- [16].…”
Section: A Background To Nfv and Radio Resource Allocationmentioning
confidence: 99%
“…Service Assurance (0,1%) represent less than a half of the papers included in the Orchestration facet. In [40], AI (Artificial Intelligence) and ML (Machine Learning) are studied in-depth, and the authors concluded that it is necessary to have special care in using these approaches due to the great complexity of data in computer networks.…”
Section: Inside the Bubbles (In-depth Analysis)mentioning
confidence: 99%
“…Artificial Intelligence algorithms can be used to aid decision making that is part of VNF placement and elasticity of resources [40]. Some of the candidate machine learning algorithms to be used are the ones related to predictions, such as linear regression.…”
Section: Self-orchestrationmentioning
confidence: 99%